'Being a mother is not child's play': The capabilities of mothers in a low‐resource setting in South Africa. (17th January 2023) - Pienaar, Michael; Marais, Lochner; Serekoane, Mosaathebe; Marais, Kobus; Cloete, Jan; Lenka, Molefi; Sharp, Carla
Abstract: Background: The importance of a child's first 1000 days has now been widely accepted by the medical fraternity. Yet, we do not know much about caring practices in low‐resource settings. Aim: This study aimed to investigate the caring capabilities of mothers in a low‐resource setting. Method: In this study, in‐depth interviews were conducted with 18 mothers with children aged 30 months or younger to better understand the arrangements, means and ends that inform developmental health in a low‐resource setting in South Africa. The study was conducted in a low‐income area, the former black township of Mangaung in Bloemfontein. The mothers were recruited via pamphlets, and two interviews followed. Because of Covid‐19, interviews took place via mobile phones, in Sesotho, the local language in the area. Trained fieldworkers conducted, translated and transcribed the interviews. We used thematic analysis and the capabilities approach as the theoretical framework to analyse the responses from the mothers. Findings: We used the following organizing themes: pregnancy and ante‐natal care, nutrition, cognitive and physical development, the home environment and access to health care. Although short‐term reactions to pregnancy were often negative, the longer‐term responses showed that the respondents have agency. Most of them could change their nutrition habits, breastfeed and receive adequate nutrition support from the public health system. Most experienced joy when their children reached milestones (cognitive and others), although they became anxious if milestones were not reached. They emphasized children's play and had dreams for their children's futures. Technology was often mentioned as playing a role in their children's development. A large proportion of the respondents had disrupted homes (because of absent or abusive fathers), but some had stable homes. Most of them showed substantial capability to overcome adverse home environments. The public health system helped them deal with their health problems and their children's health problems, although it also created anxiety in many cases. Our data show how they develop their capabilities and overcome obstacles organically in the face of resource limitations. Despite pregnancies being unexpected and unplanned and fathers being absent, the respondents accepted the pregnancy, adjusted their diets and social behaviour, showed agency by attending primary healthcare facilities and ensured that their children received the required vaccinations. Their extended families played an important role in providing care. Despite the sacrifices, the respondents expressed joy and helped their children function by eating, playing, socializing, learning and using their senses. Conclusion: Our sample of mothers have the agency to adapt to the demands of parenthood and childcare and overcome adversity. Our data support the notion that mothers are held disproportionately and unfairly responsible for achieving the first 1000 days ideals. Despite considerable curtailment of their functionings and capabilities, they nevertheless showed agency to ensure their health and their children's health. A holistic approach should consider these findings in designing policy interventions for children's developmental health. Patient and Public Contribution: We used paid fieldworkers to interact with the research participants.